2016
DOI: 10.2224/sbp.2016.44.6.973
|View full text |Cite
|
Sign up to set email alerts
|

Product status signaling as mediator between materialism and product satisfaction of Saudis and Malaysians

Abstract: We investigated the mediating role of product status signaling in the relationship between materialism and product satisfaction of Saudi and Malaysian adults. We performed structural equation modeling to analyze data from 894 Generations X and Y participants in Malaysia and Saudi Arabia, who responded to a self-administered survey. Contrary to previous research findings both from Malaysia, and from North American and other Western-culture samples, there were positive significant direct effects of materialism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Materialism and status consumption: Materialism has impact on what consumers desire from their possessions and materialistic consumers may think that it is not possible to achieve status recognition without acquiring sufficient possessions. It can be said that materialism is associated with conspicuous consumption and derived from the other's response towards the consumption rather than the product, that is, people's desires to make a show of their ability to afford goods (Kassım et al, 2016). Materialism has a strong influence on satisfaction with products that can represent status, and status consumption is a possession of a product which is because of its status (Vazifehdoost, Afshari & Goodarzi, 2014).…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Materialism and status consumption: Materialism has impact on what consumers desire from their possessions and materialistic consumers may think that it is not possible to achieve status recognition without acquiring sufficient possessions. It can be said that materialism is associated with conspicuous consumption and derived from the other's response towards the consumption rather than the product, that is, people's desires to make a show of their ability to afford goods (Kassım et al, 2016). Materialism has a strong influence on satisfaction with products that can represent status, and status consumption is a possession of a product which is because of its status (Vazifehdoost, Afshari & Goodarzi, 2014).…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
“…One of the approaches to studying people's consumption experiences has been to investigate materialism and status consumption (Jusoh, Heaney & Goldsmith, 2001;Heaney, Goldsmith & Jusoh, 2005;Goldsmith & Clark, 2012;Flynn, Goldsmith & Pollitte, 2016;Kassım et al, 2016;Minton et al, 2016). Materialism and status consumption are important personality traits underlying various consumers' behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, H7b and H7d were supported. When an advertorial is perceived as credible and entertaining by highly materialistic people, they will pay more attention to the advertorial (Flynn et al , 2016), and will be more excited and interested in further reading to doubly confirm their perceptions and evaluation of a particular product for the purpose of self-presentation and self-enhancement (Davidson et al , 2017; Kassim et al , 2016) and to fulfill their need for satisfaction (Lee and Ahn, 2016). Because the effect of perceived information and irritation on control showed insignificant difference between high and low materialists, H7a and H7c were not supported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, highly materialistic consumers will continuously acquire material possessions to meet their psychological needs to maintain happiness and life satisfaction. Kassim et al (2016) suggested that some materialists place more value on material acquisition either to cope with or satisfy feelings of uncertainty or insecurity. Under these circumstances, consumers who are not satisfied with the product information provided by an advertorial are predicted to be more excited and more likely to actively search for more relevant information about the product to develop confidence and self-enhancement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…İnsanların değerleri ve tüketim alışkanlıkları hakkında yapılan çalışmalardan birisi de materyalist değerler ve statü tüketimi araştırmalarıdır (Jusoh, Heaney ve Goldsmith, 2001;Heaney, Goldsmith ve Jusoh, 2005;Goldsmith ve Clark, 2012;Flynn, Goldsmith ve Pollitte, 2016;Kassım,Bogari, Salamah ve Zain, 2016;Minton, Kahle, Jiuan ve Tambyah, 2016). Materyalizm ve statü tüketimi, farklı tüketici davranışlarının altını çizen önemli kişilik özellikleridir.…”
Section: Introductionunclassified